Intertidal Bivalve Diversity and Fishery of the Gosthani Estuary, Bhimunipatnam, Visakhapatnam, East Coast of India - Rao, K. Rama; Jaya, P.; Priya, T. Ratna; Sandhya, T.; Amruthavarshini, N.; Chaitanya, G. Sai; Jhansi, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The results of the present investigation revealed that the occurrence of 13 species belonging to class bivalvia were dominant taxa in the Gosthani estuary. Out of 13 species 6 orders, 8 families, and 11 genera were observed from April 2023 to March 2024. The samples were obtained by handpicking, digging, and trawling with bare feet by fisher community. A field survey was conducted to collect data on mollusc species, stocks, distribution, and marketing. The bivalves were collected from the bycatch for identification, mostly based on shell morphology, hinge, interlocking dentition, etc., with reference to the standard literature In this present study data was collected and analysed from fishermen community and traders. The Crassostrea madrasensis was more dominant availability species, its contributes to highest collection 5.867 T/ year and 2.78T in Apr-23, followed by Meretrix casta 2.78 T Meretrix meretrix 1.18 T, Anadara rhombea 0.87, Tegillarca granosa 0.759 and followed by other species. According to IUCN status 13 species contributed to 53.84% are not evaluated (NE), followed by data deficient (DD) with 30.76%, and least concerned 15.38%. The monthly available bivalves at Gosthani estuary the data was comparison for abundance. The difference between the sample averages of all groups is not big enough to be statistically significant. The results of ANOVA for p-value of 0.97 indicate significant support for H0. The p-value equals to 0.231 indicates a greater support for H0.